Jenis-Jenis Kima dan Kelimpahannya di Perairan Amdui Distrik Batanta Selatan Kabupaten Raja Ampat - Absalom Wakum; Muhammad Takdir; Selfanie Talakua (Jurnal Sumberdaya Akuatik Indopasifik, 2017)
Giant clams, fauna that wellknown protected worldwide were also found in Raja Ampat. This study aimed to inventarus the giant clam species and its abundancy, and was done on March-April 2014 in Amdui that has coral reef ecosystem. Three sites study were in Ayem isle, Sawaris Bay and Sawros Bay, and the method used observation and belt transect technique. Giant clams found consisted 8 species that were T. crocea, T. maxima, T. squamosa, T .gigas, H. porcellanus, H. hippopus, T. tevoroa dan T.derasa. The highest abundancy of giant clams was in station I dominated by T. maxima with percentage 48.387 %, and then the lowest abundancy was T.squamosa (3.225 %) also the density of T.squamosa only 0.002 individu/m2 . At station II, the highest abundancy was T. maxima (38.805 %) and the lowest T. squamosa 2.985%. The density however, ranged from T.maxima 0.004 to 0.052 individu/m2. At station III, T.crocea dominantly covered at 139.860%, and the lowest abundancy was T.tevoroa 0.699%, and the highest density was T.crocea 0.112 individu/m2 .